2005
DOI: 10.1111/j.1540-8183.2005.04066.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a New Thrombus Extraction Catheter (The Pronto®) in the Treatment of Acute Myocardial Infarction

Abstract: The finding of an intracoronary thrombus at the time of coronary angiography is common in patients presenting with an acute coronary syndrome. Pharmacologic and mechanical treatment strategies have been developed and reported to facilitate the treatment of the thrombus along with a percutaneous coronary intervention. We report a case in which a Pronto thrombectomy catheter was utilized to facilitate thrombus removal prior to the placement of a coronary stent in a patient who developed postinfarct angina and pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
5
0
2
Order By: Relevance
“…Tubes were immediately inverted five times to blend in the clot activator and blood was allowed to clot for 30 min prior to centrifugation at 1000× g for 15 min. Plasma was prepared from total blood aspirated from the coronary artery with a Pronto® V3 thrombus extraction catheter (Vascular Solutions, Minneapolis, MN, USA) 10 and filtered through a cell strainer (pore filter size 40 μm, BD Falcon). In parallel, systemic blood was drawn from the femoral sheath.…”
Section: Methodsmentioning
confidence: 99%
“…Tubes were immediately inverted five times to blend in the clot activator and blood was allowed to clot for 30 min prior to centrifugation at 1000× g for 15 min. Plasma was prepared from total blood aspirated from the coronary artery with a Pronto® V3 thrombus extraction catheter (Vascular Solutions, Minneapolis, MN, USA) 10 and filtered through a cell strainer (pore filter size 40 μm, BD Falcon). In parallel, systemic blood was drawn from the femoral sheath.…”
Section: Methodsmentioning
confidence: 99%
“…Besides standard procedures to decrease the risk of thrombus occlusion, mechanical treatments of intracoronary thrombi involve the use of specially designed catheters to perform thrombectomy or the employment of distal protection devices to prevent the thrombus from embolizing toward the distal coronary bed (2). In spite of their use in the clinical practice, these techniques present some limitations.…”
mentioning
confidence: 99%
“…They include a distal tip with either a single central lumen (2,5) or a combination of central and side holes (6). Different solutions, mainly based on different distal tip shapes, have been suggested (2,7,8), but their effectiveness has not been really demonstrated. A number of clinical trials (5,6,9) and in vitro tests (10,11) are reported in the literature.…”
mentioning
confidence: 99%
“…Alguns dispositivos têm sido utilizados para evitar ou diminuir estes fenômenos de microembolizações, com resultados controversos [13][14][15] . Metanálise envolvendo 21 trials e 3721 pacientes, onde 50,4% deles usaram algum tipo de dispositivo, demonstrou que este grupo de pacientes teve melhor perfusão miocárdica, menos embolização distal, contudo, ainda sem melhora na sobrevida em 30 dias 16 .…”
Section: Discussionunclassified